2015
DOI: 10.1002/jmv.24438
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of three echovirus strains on cell lysis and insulin secretion in beta cell derived lines

Abstract: In an earlier study, infection of human pancreatic islets with epidemic strains of echovirus (E4, E16, E30), with proven but differently ability to induce islet autoimmunity, resulted either in a severe damage (i.e., E16 and E30) or proceeded without visible changes in infected islets (i.e., E4). In this study, the ability of these strains to replicate in beta cells and the consequence of such an infection for beta cell lysis and beta cell function was studied in the pancreatic beta cell lines INS-1, MIN6, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have shown that strains of E16, isolated from patients with meningitis, resulted in the development of diabetes-related islet autoantibodies [18,19,25]. In addition, E16 is able to replicate in explanted human islets and clonal beta cell lines, thus concluding that E16 can target pancreatic endocrine cells [26,27].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that strains of E16, isolated from patients with meningitis, resulted in the development of diabetes-related islet autoantibodies [18,19,25]. In addition, E16 is able to replicate in explanted human islets and clonal beta cell lines, thus concluding that E16 can target pancreatic endocrine cells [26,27].…”
Section: Discussionmentioning
confidence: 98%
“…Human enteroviruses replication in islets and ductal—but not in acinar—cells has been demonstrated in earlier reports [ 3 , 18 , 19 , 32 , 33 ], suggesting that human exocrine pancreas may not represent a target of HEV. Accordingly, we previously showed by virus titration studies, immunoreactivity of HEV VP1 protein and mRNA expression of innate immunity genes that E16 and E30 can productively infect both primary human islets and β cell-derived lines [ 21 , 22 ]. The present study confirms this observation by revealing an increase in viral titer when islets were infected with E16 and E30.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the aforementioned studies have focused mainly on CVB, and there has been no attempt to assess the possible tropism of echovirus towards exocrine cells. Although we previously demonstrated that strains of E16 and E30 with a proven association with islet autoimmunity were able to replicate in explanted human islets and β cell-derived lines [ 20 , 21 , 22 ], their effect on human exocrine cells has never been tested. Interestingly, maternal infection with E6, a closely related echovirus strain, was associated with the induction of coexisting neonatal type 1 diabetes and exocrine pancreatic insufficiency in a Finnish report [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the medium was discarded, cells were preincubated with Krebs‐Ringer bicarbonate HEPES (KRBH) buffer (140 mmol/L NaCl, 3.6 mmol/L KCl, 0.5 mmol/L NaH 2 PO 4 , 0.5 mmol/L MgSO 4 , 1.5 mmol/L CaCl 2 , 2 mmol/L NaHCO 3 , 10 mmol/L HEPES, and 0.1% bovine serum albumin) for 2 hours at 37°C. According to a previous report, morin was added to the KRBH buffer containing various concentrations of glucose. The plate was then incubated for 2 hours at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…According to a previous report, 33 morin was added to the KRBH buffer containing various concentrations of glucose. The plate was then incubated for 2 hours at 37°C.…”
Section: Glucose-stimulated Insulin Secretion (Gsis)mentioning
confidence: 99%